Associations of maternal iron deficiency with malaria infection in a cohort of pregnant Papua New Guinean women - Holger W. Unger; Andie Bleicher; Maria Ome-Kaius; Elizabeth H. Aitken; Stephen J. Rogerson (Malaria Journal, 2022)
Abstract Background Iron deficiency (ID) is common in malaria-endemic settings. Intermittent preventative treatment of malaria in pregnancy (IPTp) and iron supplementation are core components of antenatal care in endemic regions to prevent adverse pregnancy outcomes. ID has been associated with reduced risk of malaria infection, and correspondingly, iron supplementation with increased risk of malaria infection, in some studies. Methods A secondary analysis was conducted amongst 1888 pregnant women enrolled in a malaria prevention trial in Papua New Guinea. Maternal ID was defined as inflammation-corrected plasma ferritin levels < 15 μg/L at antenatal enrolment. Malaria burden (Plasmodium falciparum, Plasmodium vivax) was determined by light microscopy, polymerase chain reaction, and placental histology. Multiple logistic and linear regression analyses explored the relationship of ID or ferritin levels with indicators of malaria infection. Models were fitted with interaction terms to assess for modification of iron-malaria relationships by gravidity or treatment arm. Results Two-thirds (n = 1226) and 13.7% (n = 258) of women had ID and peripheral parasitaemia, respectively, at antenatal enrolment (median gestational age: 22 weeks), and 18.7% (120/1,356) had evidence of malaria infection on placental histology. Overall, ID was associated with reduced odds of peripheral parasitaemia at enrolment (adjusted odds ratio [aOR] 0.50; 95% confidence interval [95% CI] 0.38, 0.66, P < 0.001); peripheral parasitaemia at delivery (aOR 0.68, 95% CI 0.46, 1.00; P = 0.050); and past placental infection (aOR 0.35, 95% CI 0.24, 0.50; P < 0.001). Corresponding increases in the odds of infection were observed with two-fold increases in ferritin levels. There was effect modification of iron-malaria relationships by gravidity. At delivery, ID was associated with reduced odds of peripheral parasitaemia amongst primigravid (AOR 0.44, 95% CI 0.25, 0.76; P = 0.003), but not multigravid women (AOR 1.12, 95% CI 0.61, 2.05; P = 0.720). A two-fold increase in ferritin associated with increased odds of placental blood infection (1.44, 95% CI 1.06, 1.96; P = 0.019) and active placental infection on histology amongst primigravid women only (1.24, 95% CI 1.00, 1.54; P = 0.052). Conclusions Low maternal ferritin at first antenatal visit was associated with a lower risk of malaria infection during pregnancy, most notably in primigravid women. The mechanisms by which maternal iron stores influence susceptibility to infection with Plasmodium species require further investigation. Trial registration